A divergent [5+2] cascade approach to bicyclo[3.2.1]octanes: facile synthesis of ent-kaurene and cedrene-type skeletons. Issue 60 (12th July 2017) - He, Chi; Bai, Zengbing; Hu, Jialei; Wang, Bingnan; Xie, Hujun; Yu, Lei; Ding, Hanfeng
Abstract : A divergent [5+2] cascade approach to bicyclo[3.2.1]octanes was described, enabling the rapid synthesis of diversely functionalized ent -kaurene and cedrene-type skeletons. Abstract : A solvent-dependent oxidative dearomatization-induced divergent [5+2] cascade approach to bicyclo[3.2.1]octanes was described. This novel protocol enables a facile synthesis of a series of diversely functionalized ent -kaurene and cedrene-type skeletons in good yields and excellent diastereoselectivities.